Estimates for the modulus of a Cauchy-type integral and its derivatives - Gerus, O. F. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
In a domain bounded by a closed rectifiable Jordan curve, we obtain estimates for the modulus of a Cauchy-type integral and its derivatives in terms of the contour moduli of smoothness of the integrand and a metric characteristic of the curve.